Urgensi Keberadaan Motif Dalam Tindak Pidana Pembunuhan Berencana Berdasarkan Perspektif Hukum Pidana : Urgensi Keberadaan Motif Dalam Tindak Pidana Pembunuhan Berencana Berdasarkan Perspektif Hukum Pidana - Anzhalna, Puja (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2023)
This research examines the pressing nature of motive in the crime of premeditated murder From a criminal law perspective. The goal this research is to determine how important the motive in the crime of premeditated murder. This research used a contextualized approach, normative juridical research methodology, and an analysis of laws and regulations. Based on the research's observations, it is not essential to prove in court that a defendant had motives for committing planned murder. The definition of the offense under Section 340 of the Criminal Code does not include a motivational component. Keywords: Crime of Premeditated Murder; Motive; Urgency